Catalytic one-pot diastereoselective Michael-initiated ring-closure of methyl ketones with 3-bromochromones: synthesis of cyclopropa[b]chromanones - Sousa, Joana L. C. (2016)
A one-pot diastereoselective base-catalyzed Michael-initiated ring-closure (MIRC) of activated methyl ketones with 3-bromochromones to give cyclopropa[b]chromanones is described. Three asymmetric centres are generated in the new cyclopropa[b]chromanone skeleton. Stereochemistry studies based on NMR spectroscopy and single-crystal X-ray diffraction analysis revealed the trans configuration of the cyclopropane ring, with the (1R,1aS,7aR)/(1S,1aR,7aS) pair of enantiomers, as was further confirmed by chiral HPLC. The use of acetone in our reaction produced a 1-acetyl-substituted cyclopropa[b]chromanone that can undergo a subsequent MIRC reaction with a second molecule of 3-bromochromone to give the first described 1,1′-carbonylbis(cyclopropa[b]chromanone) dimers as a meso form.